Otonomi Sebagai Sebuah Pilihan - Linda Suryakusuma (Respons: Jurnal Etika Sosial, 2008)
Abstract: The introduction of autonomy as a fundamental important normative concept is probably the most important breakthrough in modern bioethics. However, when physicians and indeed, bioethicists, begin to assume that “autonomy is what we know is best for the patient”, it is doubtful whether in such a situation, autonomy as a principle is autonomy indeed and not some paternalistic conception of autonomy that is being imposed on patients. The main aim of this paper is to argue in favor of regarding autonomy as a choice. It argues that autonomy is a social concept, not an individual one. Therefore support for regarding it as a choice should naturally be found in autonomy’s social context, more specifically in its relationship with three major social determinants of contemporary medical practices, namely: freedom, culture and trust. Analysis of each of these relationships reveals the conclusion that the only “autonomous” way to foster autonomy is by regarding it as a choice. In other words, the first decision a patient should make is whether or not he wants to use his right for medical decision making. Kata Kunci: Otonomi, pilihan, kebebasan, kebudayaan, kepercayaan, tantangan modern